Managing the Current Situation of Young People in National and European Context in Terms of Their Employment - Braica, Alexandra Patricia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Assessment and research into this phenomenon of social marginalization and social exclusion of young people at both national and European levels has as a target to find methods of prevention and reduction of this phenomenon and understand the fact that it is only through communication, debates and dialog that will we be able to establish benchmarks for joint action. Young people are one of the age segments which are most affected by the economic recession. It is also accepted that in each of the Member States of the EU, despite different circumstances and levels of economic development, major issues faced by young people are the same: from access to essential services (such as education and health) and up to their integration into the labour market with a view to achieving a higher standard of living. The decision makers are constantly interested in solving these stringent problems, which can be found in the policies and strategies for economic recovery and fighting the austerity measures adopted by the Member States of the EU, through a series of programs that have as main objectives combating unemployment and poverty among young people and providing opportunities for more active involvement in their community life: political, social, economic, cultural. In Romania, the problem of young people constitutes an issue of major importance for the Government, which has drawn up for the first time an Integrated Strategy of Romania with regard to young people called "National Strategy for Youth 2014-2020"1, with particular emphasis on the first role that education must play in this context. Examples of solutions identified by the governors are: an increase in public funding for mentoring programs, for the prevention of school dropout rates, establishment of differentiated educational offers, training schemes designed to eliminate lack of qualification in young people, in such a way as to maintain a competitive and well-prepared generation in the country.